Serological Evaluation of Vitamin B12 and Homocysteine Levels in Colorectal Cancer Patients and their Relationships to Global DNA Methylation and P53 Expression - Ahmed, Dalya F.; AL-Jumaily, Rakad M. Kh; Obaid, Mohammed F. (Iraqi Journal of Science, 2026)
Colorectal cancer (CRC) is the most deadly disease, and has a high rate of mortality. Interestingly, biological biomarkers is binifical in the early diagnosis and treatment of CRC. This study was designed to measure the changes in the Vitamin B12 (Vit. B12) and Homocysteine (Hcy) at serological levels according to the clinical-outcome of CRC patients as well as to examine its correlation with global 5-methylcytosine (5mC) and P53 expression that associated with progression of CRC disease. The current study was included 30 healthy volunteers who served as controls and 60 patients with CRC. The blood samples were collected and serum levels of Vit. B12 and Hcy were measured using ELISA assay. DNA and RNA were also extracted, and the levels of global DNA methylation and P53 expression were evaluated. The results revealed a significant increases in Hcy levels in CRC patients compared to healthy controls was observed (373.67±17.67 and 83.16±6.11 pg/ml), respectively. In contrast , no significant change was observed in the levels of Vit. B12 in CRC patients compared to healthy controls (565.66±32.21 and 1178.76±28.93 pg/ml), respectively. They were accompanied by significantly reduced levels of 5mC in CRC patients in compared to controsl (0.31±0.02 and 0.46±0.03, respectively), with a positive correlation between 5mC and the different stages of CRC. In addition, the results showed a positive correlation between 5mC and Vit. B12 but not Hcy. The results of P53 expression showed no significant differences concerninig to healthy control. Furthermore, there was no correlation between Hcy, global DNA methylation, and P53 gene expression. In conclusion,  the present study indicates that the changes in Vit.B12, Hcy, and 5mC levels at the different pathogenesis outcomes of CRC disease play an important role as a risk factor for CRC progression.